Effects of symmetrical roof shape on pressure coefficient difference in isothermal condition - Boroojerdian, Mohammad Mahdi (2015)
Wind driven ventilation techniques mainly rely on the design and geometry of the roof and structure. Venturi shaped roof uses two airfoil like cross section, one mounted on top of the other, to increase the wind speed in the venturi contraction thus reducing the static pressure. This negative pressure induces natural ventilation in building by sucking the air out through a duct connected to the roof. The influence of the contraction resistance referred as wind blocking effect is the most important effect for reducing the venturi effect of the roof. If the passage width decreases more wind will only flow around and over the roof. Hence the roof is extremely dependent on its geometrical characteristics for its optimum performance. The objective of this study is to conduct a study on the geometric characteristics of the roof and investigate the impact of various geometries and configurations to propose an optimum venturi roof geometry suitable for the hot and humid regions of Malaysia. To achieve this, three models with different roof shapes were chosen and tested in the wind tunnel. This study compares performance of different roof models shape 1 (Shallow ellipse), shape 2 (ellipse) and shape 3 (hemisphere) in low speed wind tunnel and compares the pressure coefficient (Cp) values at the center of the roof at its contraction, as an indication for higher performance and ventilation flow rates. The results show that shape 1 (Shallow ellipse) outperformed shape 2 (ellipse) and shape 3 (hemisphere). However when the upper part of the roof is unmounted, the hemisphere without the upper part performs the best and shape 2 without upper part of roof and shape 1 without the upper part of roof perform the worst. This is important at conditions that narrow supporting is not possible for the upper disc. Shape 3 without the upper part also called the simple dome shows 70% of the performance of shape 1(shallow ellipse). When commissioning of shape 1 is not possible, the dome would be the best option since there is no upper part and no supporting pillars are required thus alleviating construction. The results of this experimental study is believed to aid architects and designers of tall buildings with roof designs in order to get the most out of the wind for natural ventilation.